On the shock behaviour and response of Ovis Aries vertebrae - Wood, David C.; Appleby-Thomas, Gareth J.; Fitzmaurice, Brianna C.; Franceskides, Constantinos; Shanker, Tobias; Zioupos, Peter; Samra, Amarjit (European Society of Biomechanics, 2016)
When investigating a biological system during shock loading, it is best practice to isolate different components to fully comprehend each individual part [1,2] before building up the system as a whole. Due to the high acoustic impedance of bone in comparison to other biological tissues [3] the majority of the shock will be transmitted into this medium, and as such can cause large amounts of damage to other parts of the body potentially away from the impact area.